APPLICATIONS PAYROLL PT. XYZ BY USING MICROSOFT VISUAL FOXPRO 9.0 - Indra Purnama Alam; Susi Widayati., SKom., MM (Jurnal Sistem Informasi, 2010)
Microsoft Visual FoxPro 9.0 is a software used for data processing. Data processingdone with the database as a place to store data.Like PT Payroll in general. XYZ also has a lot of employees so that employees on thepayroll processing reports each month. To control the salaries of employees andfacilitate in making the report used language Microsoft Visual FoxPro 9.0.With this application, it is expected to be useful in improving the performance ofemployees. This is because the performance of the employees can not be separatedfrom data and information quickly and accurately so that the time it takes to be a littlemore.